Social Eavesdropping in Zebrafish - Abreu, Rodrigo Manuel Abril (2016)
Group living animals may eavesdrop on signalling interactions between conspecifics. This enables them to collect adaptively relevant information about others, without incurring in the costs of first-hand information acquisition. Such ability, aka social eavesdropping, is expected to impact Darwinian fitness and hence predicts the evolution of cognitive processes that enable social animals to use social information available in the environment.(...)